A method for preparing a sulfide solid-state battery in which an SEI layer containing Li3PS4 is generated in situ
Patent Information
- Application Number
- CN202611300827.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]在此,我们设计一种硫化物与聚合物复合的固态电解质以解决锂枝晶和界面阻抗大等问题
[0020]1.高锂离子迁移率:咔唑共轭网络 + 柔性硅烷链协同,最优体系迁移率可达0.92,远高于纯 PEO 空白样品 0.41;
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sulfide solid electrolyte preparation technology, specifically relating to a method for preparing a sulfide solid battery containing a Li3PS4 SEI layer in situ. Background Technology
[0002] To achieve high energy density in lithium-ion batteries while also ensuring high safety, long lifespan, fast charging, low cost, and good performance over a wide temperature range, all-solid-state batteries are currently one of the most promising strategies. However, the realization of lithium metal anode all-solid-state batteries faces significant challenges, such as severe interfacial reactions, lithium dendrite formation, and high interfacial impedance. To overcome these challenges, constructing a chemically / electrochemically stable, mechanically compatible, lithium-ion conductive, and electronically insulating SEI film at the interface between the electrolyte and lithium metal is considered an effective measure.
[0003] For example, patent CN114464876B discloses a sulfide / polymer composite solid electrolyte and its preparation method. The method includes the following steps: first, a boric acid-modified sulfide lithium-ion battery solid electrolyte is obtained through sand milling and heat treatment; then, a polymer solid electrolyte is coated onto its surface through heat treatment. The main advantage of this invention is that by adding boric acid to modify the sulfide solid electrolyte, the boric acid melts during calcination and uniformly coats the surface of the sulfide solid electrolyte, effectively improving the structural stability of the sulfide.
[0004] Here, we design a sulfide-polymer composite solid electrolyte to address issues such as lithium dendrite formation and high interfacial impedance. Specifically, lithium polyphosphoric sulfide (LPS) is introduced as an additive into a polyethylene oxide (PEO)-based electrolyte, and an ideal SEI layer is generated in situ through the synergistic reaction of LPS, PEO, and metallic lithium. Summary of the Invention
[0005] The objective of this invention is to introduce Li3PS4 (LPS) sulfidation additive into a PEO polymer electrolyte system, combined with a carbazole-organosilicon-ferrocene composite ion-conducting agent prepared by platinum-catalyzed hydrosilylation; during the low-current pre-formation process of the battery, LPS undergoes an in-situ interfacial reaction with metallic lithium to generate a dense SEI passivation layer rich in Li3PS4 and mechanically flexible; the additive constructs a continuous lithium-ion transport network, improves mobility and low-temperature conductivity, inhibits lithium dendrite growth, reduces interfacial impedance, and extends the cycle life of solid-state batteries.
[0006] The technical solution of this invention: A method for preparing a solid-state battery containing a Li3PS4-containing SEI layer sulfide, characterized by comprising the following steps:
[0007] 1. In an anhydrous nitrogen-sealed reaction system, lithium sulfide (Li2S), elemental sulfur (S), and phosphorus pentasulfide (P2S5) were weighed according to their mass fractions, and ultra-dry acetonitrile solvent was added. The mixture was then stirred at room temperature under a sealed environment to prepare a uniform yellow complex solution of Li3PS4. Water vapor and oxygen were completely isolated throughout the process.
[0008] B. Preparation of composite polymer sulfurized electrolyte by casting: PEO and LiTFSI lithium salts were pre-dehydrated under vacuum; PEO and LiTFSI were dissolved in ultra-dry acetonitrile and stirred at a constant temperature to form a base solution; the above-mentioned Li3PS4 complex solution and silicon organic ionic conductivity additive were added to the base solution and stirred thoroughly at a constant temperature; the mixed solution was cast onto a PTFE substrate and dried in sections at room temperature and under vacuum under nitrogen protection to obtain a flexible composite solid electrolyte membrane; C. Battery assembly and in-situ SEI formation: Lithium / / lithium symmetric batteries were assembled in an argon glove box with lithium metal as the negative electrode. Low-current pre-formation induced the in-situ formation of a stable SEI passivation layer containing Li3PS4 on the surface of the lithium metal; lithium ion mobility, room temperature ionic conductivity, and critical current density were tested using an electrochemical workstation.
[0009] In a preferred embodiment of the present invention, step A comprises lithium sulfide, elemental sulfur, and phosphorus pentasulfide in a mass ratio of 23-69:32-96:111-333. In a preferred embodiment of the present invention, step A further comprises adding 300-800 parts by mass of ultra-dry acetonitrile and stirring at room temperature in a sealed environment for 6-12 hours. In a preferred embodiment of the present invention, step B comprises vacuum drying of PEO at 50-60°C for 36-72 hours; and vacuum drying of LiTFSI at 100-120°C for 36-72 hours. In a preferred embodiment of the present invention, the mass ratio of PEO, LiTFSI, and ultra-dry acetonitrile is 60-80:2.8-5.6:150-250, and the base adhesive is stirred at 50-60°C for 6-18 hours. In a preferred embodiment of the present invention, the mass ratio of Li3PS4 solution, additives, and base adhesive is 0-20:0.1-0.2:100-200. As a preferred embodiment of the present invention, the raw materials and preparation process of the ionic conductivity additive are as described in claim 9, with anhydrous nitrogen protection throughout the process. As a preferred embodiment of the present invention, the mixed composite adhesive is continuously stirred at 50-60°C for 6-18 hours. As a preferred embodiment of the present invention, the cast film is dried at room temperature under nitrogen protection for 36-72 hours, followed by drying in a vacuum oven at 50-60°C for 36-72 hours to completely remove the solvent.
[0010] Reaction mechanism
[0011] 1. Synthesis mechanism of organosilicone carbazole adjuvant
[0012] Under anhydrous nitrogen and platinum catalysis, the Si-H bond of (4-vinylphenyl)dimethylsilane undergoes hydrosilylation with the carbon-carbon double bond of N-vinylcarbazole to form a flexible siloxane-carbazole copolymer; the 1,1'-di(dimethylsilyl)ferrocene silane-hydrogen groups simultaneously participate in crosslinking, introducing trace amounts of iron metal centers to construct a three-dimensional organosilicon conjugated network; chloroplatinic acid is used to remove water in advance to avoid hydrolysis and disruption of the addition reaction.
[0013] 2. Mechanism of Lithium-ion Conductivity Enhancement
[0014] Carbazole conjugated units form continuous lithium-ion transport channels through π-π stacking; flexible silane segments reduce the polymer's glass transition temperature (Tg), weaken PEO segment entanglement, and significantly improve the low-temperature lithium-ion migration rate; trace iron centers moderately regulate the interface electron distribution without inducing electron conduction dendrites.
[0015] 3. In-situ Li3PS4-type SEI core generation mechanism
[0016] Under the action of a small pre-formation current, Li3PS4 in the electrolyte undergoes a controllable interfacial reduction reaction with the lithium metal anode, generating a dense, flexible, and electronically insulating composite SEI film in situ on the lithium sheet surface. The SEI is rich in Li3PS4 phase, possesses high lithium-ion conductivity, isolates the PEO matrix from direct contact with lithium metal, terminates continuous oxidation side reactions, and mechanically buffers the volume deformation of lithium deposition, inhibiting lithium dendrite puncture.
[0017] 4. Synergistic effect mechanism of adjuvants and LPS
[0018] Silicon-based organic additives enhance the bulk ion conductivity and reduce polarization; Li3PS4 is responsible for constructing a stable passivation interface in situ. The combination of the two simultaneously solves the two core defects of poor bulk electrolyte conductivity and unstable lithium metal interface, resulting in a performance improvement far exceeding that of single modification methods.
[0019] Technical effect
[0020] 1. High lithium-ion mobility: The carbazole conjugated network and flexible silane chain work together to achieve an optimal system mobility of 0.92, which is much higher than the 0.41 of the pure PEO blank sample;
[0021] 2. Significantly improved room temperature ionic conductivity: The modified composite electrolyte exhibits a room temperature conductivity of up to 0.0076 S / cm, which is more than 9 times that of the blank system;
[0022] 3. Excellent resistance to lithium dendrite formation: The in-situ Li3PS4SEI passivation layer can significantly increase the critical current density and suppress dendrite precipitation;
[0023] 4. Long-term interface stability: The SEI layer isolates side reactions, resulting in minimal increase in interface impedance during long-term cycling and significantly extending battery cycle life;
[0024] 5. Mild preparation process: Solution casting is compatible with existing thin film production lines, raw materials are readily available, and preparation can be completed using conventional equipment with anhydrous nitrogen, showing great potential for industrialization. Detailed Implementation
[0025] The present invention will be described in detail below with reference to specific embodiments.
[0026] Example 1
[0027] A method for preparing an in-situ generated SEI layer sulfide solid-state battery containing Li3PS4, characterized by comprising the following steps:
[0028] A. Weigh 23g of lithium sulfide, 32g of sulfur, and 111g of phosphorus pentasulfide according to a certain mass ratio as raw materials for preparing solid electrolytes. Add 300g of acetonitrile solvent and stir thoroughly at room temperature for 6 hours until the reaction is complete, forming a uniform yellow solution.
[0029] B. The composite solid electrolyte membrane was prepared using conventional solution casting technology. Before preparation, the raw materials were dried: polyethylene oxide was vacuum dried at 50°C for 36 hours, and lithium bis(trifluoromethanesulfonyl)imide was vacuum dried at 100°C for 36 hours. 60g of polyethylene oxide, 0.1g of ionic conductivity additive, and 2.8g of lithium bis(trifluoromethanesulfonyl)imide were dissolved in 150g of acetonitrile and continuously stirred at 50°C for 6 hours to form a uniform PEO / LiTFSI solution. The solution was continuously stirred at 50°C for 6 hours, and the final solution was cast into a polytetrafluoroethylene plate and dried at room temperature for 36 hours. Then, it was dried in a vacuum oven at 50°C for 36 hours to obtain the sulfide solid electrolyte.
[0030] The method for preparing the ionic conductivity enhancer is as follows:
[0031] Mass ratio of reactants
[0032] 1. (4-Vinylphenyl)dimethylsilane: 16g
[0033] 2. N-vinylcarbazole: 19g
[0034] 3. 1,1'-Di(dimethylsilyl)ferric, CAS: 1295-15-4: 0.3g
[0035] 4. Tetrahydrofuran (THF): 160g
[0036] Preparation steps
[0037] T1 catalyst activation
[0038] Add 0.1g of chloroplatinic acid (H2PtCl6·6H2O) and 5g of isopropanol to the reactor, and stir at 40°C for 30 minutes to form an active catalyst solution.
[0039] T2 Hydrosilylation Reaction
[0040] Add (4-vinylphenyl)dimethylsilane, N-vinylcarbazole, and 1,1'-di(dimethylsilyl)ferric sequentially, and start stirring at 250 rpm. Heat the system to 50°C at a rate of 3°C / min, and react for 2 hours under nitrogen protection.
[0041] T3 Product Post-processing
[0042] After the reaction was completed, THF and isopropanol were removed by vacuum distillation. The residue was washed three times with ethanol and dried under vacuum (60°C, 12 hours) to obtain the auxiliary agent.
[0043] C. Assembled into a lithium / / lithium symmetric battery, its lithium-ion mobility was tested to be 0.64, ionic conductivity to be 0.0024 S / cm, and critical current density to be 0.33 mA / cm. 2 .
[0044] Example 2
[0045] A method for preparing an in-situ generated SEI layer sulfide solid-state battery containing Li3PS4, characterized by comprising the following steps:
[0046] A. Weigh 46g of lithium sulfide, 64g of sulfur, and 222g of phosphorus pentasulfide according to a certain mass ratio as raw materials for preparing solid electrolytes. Add 500g of acetonitrile solvent and stir thoroughly at room temperature for 12 hours until the reaction is complete, forming a uniform yellow solution.
[0047] B. The composite solid electrolyte membrane was prepared using conventional solution casting technology. Before preparation, the raw materials were dried: polyethylene oxide was vacuum dried at 55°C for 48 hours, and lithium bis(trifluoromethanesulfonyl)imide was vacuum dried at 110°C for 48 hours. 70g of polyethylene oxide and 4.2g of lithium bis(trifluoromethanesulfonyl)imide were dissolved in 200g of acetonitrile and continuously stirred at 55°C for 12 hours to form a homogeneous PEO / LiTFSI solution. 10g of Li3PS4 complex solution and 0.15g of ionic conductivity additive were added to 150g of the PEO / LiTFSI solution, and the mixture was continuously stirred at 55°C for 12 hours. The final solution was cast into a polytetrafluoroethylene (PTFE) plate and dried at room temperature for 48 hours, then dried in a vacuum oven at 55°C for 48 hours to obtain the sulfide solid electrolyte. The solution was continuously stirred at 55°C for 12 hours, then cast into a polytetrafluoroethylene plate and dried at room temperature for 48 hours. Finally, it was dried in a vacuum oven at 55°C for 48 hours to obtain a sulfide solid electrolyte.
[0048] The method for preparing the ionic conductivity additive is as follows: according to the mass ratio of the reactants...
[0049] 1. (4-Vinylphenyl)dimethylsilane: 24g
[0050] 2. N-vinylcarbazole: 19.5g
[0051] 3. 1,1'-Di(dimethylsilyl)ferric, CAS: 1295-15-4: 1g
[0052] 4. Tetrahydrofuran (THF): 200g
[0053] Preparation steps
[0054] T1 catalyst activation
[0055] Add 0.2g of chloroplatinic acid (H2PtCl6·6H2O) and 6g of isopropanol to the reactor, and stir at 40°C for 30 minutes to form an active catalyst solution.
[0056] T2 Hydrosilylation Reaction
[0057] Add (4-vinylphenyl)dimethylsilane, N-vinylcarbazole, and 1,1'-di(dimethylsilyl)ferric sequentially, and start stirring at 300 rpm. Heat the system to 55°C at a rate of 4°C / min, and react for 3 hours under nitrogen protection.
[0058] T3 Product Post-processing
[0059] After the reaction was completed, THF and isopropanol were removed by vacuum distillation. The residue was washed three times with ethanol and dried under vacuum (60°C, 12 hours) to obtain the auxiliary agent.
[0060] C. Assembled into a lithium / / lithium symmetric battery, its lithium-ion mobility was tested to be 0.72, ionic conductivity to be 0.0045 S / cm, and critical current density to be 0.54 mA / cm. 2 .
[0061] Example 3
[0062] A method for preparing an in-situ generated SEI layer sulfide solid-state battery containing Li3PS4, characterized by comprising the following steps:
[0063] A. Weigh 69g of lithium sulfide, 96g of sulfur, and 333g of phosphorus pentasulfide according to a certain mass ratio as raw materials for preparing solid electrolytes. Add 800g of acetonitrile solvent and stir thoroughly at room temperature for 18 hours until the reaction is complete, forming a uniform yellow solution.
[0064] B. The composite solid electrolyte membrane was prepared using conventional solution casting technology. Before preparation, the raw materials were dried: polyethylene oxide was vacuum dried at 60°C for 72 hours, and lithium bis(trifluoromethanesulfonyl)imide was vacuum dried at 120°C for 72 hours. 80g of polyethylene oxide and 5.6g of lithium bis(trifluoromethanesulfonyl)imide were dissolved in 250g of acetonitrile and continuously stirred at 60°C for 18 hours to form a homogeneous PEO / LiTFSI solution. 20g of Li3PS4 complex solution and 0.2g of ionic conductivity enhancer were added to 200g of the PEO / LiTFSI solution, and the mixture was continuously stirred at 60°C for 18 hours. The final solution was cast into a polytetrafluoroethylene (PTFE) plate and dried at room temperature for 72 hours, then dried in a vacuum oven at 60°C for 72 hours to obtain the sulfide solid electrolyte. The solution was continuously stirred at 60°C for 18 hours, then cast into a polytetrafluoroethylene plate and dried at room temperature for 72 hours. Finally, it was dried in a vacuum oven at 60°C for 72 hours to obtain a sulfide solid electrolyte.
[0065] Mass ratio of reactants
[0066] 1. (4-Vinylphenyl)dimethylsilane: 32g
[0067] 2. N-vinylcarbazole: 20g
[0068] 3. 1,1'-Di(dimethylsilyl)ferric, CAS: 1295-15-4: 1.5g
[0069] 4. Tetrahydrofuran (THF): 250g
[0070] Preparation steps
[0071] T1 catalyst activation
[0072] Add 0.3g of chloroplatinic acid (H2PtCl6·6H2O) and 8g of isopropanol to the reactor, and stir at 40°C for 30 minutes to form an active catalyst solution.
[0073] T2 Hydrosilylation Reaction
[0074] Add (4-vinylphenyl)dimethylsilane, N-vinylcarbazole, and 1,1'-di(dimethylsilyl)ferric sequentially, and start stirring at 350 rpm. Heat the system to 60°C at a rate of 5°C / min, and react for 4 hours under nitrogen protection.
[0075] T3 Product Post-processing
[0076] After the reaction was completed, THF and isopropanol were removed by vacuum distillation. The residue was washed three times with ethanol and dried under vacuum (60°C, 12 hours) to obtain the auxiliary agent.
[0077] C. Assembled into a lithium / / lithium symmetric battery, its lithium-ion mobility was tested to be 0.92, ionic conductivity to be 0.0076 S / cm, and critical current density to be 1 mA / cm. 2 .
[0078] Comparative Example 1
[0079] A method for preparing an in-situ generated SEI layer sulfide solid-state battery containing Li3PS4, characterized by comprising the following steps:
[0080] A. Weigh 23g of lithium sulfide, 32g of sulfur, and 111g of phosphorus pentasulfide according to a certain mass ratio as raw materials for preparing solid electrolytes. Add 300g of acetonitrile solvent and stir thoroughly at room temperature for 6 hours until the reaction is complete, forming a uniform yellow solution.
[0081] B. The composite solid electrolyte membrane was prepared using conventional solution casting technology. Before preparation, the raw materials were dried: polyethylene oxide was vacuum dried at 50°C for 36 hours, and lithium bis(trifluoromethanesulfonyl)imide was vacuum dried at 100°C for 36 hours. 60g of polyethylene oxide and 2.8g of lithium bis(trifluoromethanesulfonyl)imide were dissolved in 150g of acetonitrile and stirred continuously at 50°C for 6 hours to form a uniform PEO / LiTFSI solution. The solution was stirred continuously at 50°C for 6 hours, and the final solution was cast into a polytetrafluoroethylene plate and dried at room temperature for 36 hours. Then, it was dried in a vacuum oven at 50°C for 36 hours to obtain the sulfide solid electrolyte.
[0082] C. Assembled into a lithium / / lithium symmetric battery, its lithium-ion mobility was tested to be 0.41, ionic conductivity to be 0.0008 S / cm, and critical current density to be 0.01 mA / cm. 2 .
[0083] Group Modification scheme Lithium-ion mobility Ionic conductivity (S / cm) <![CDATA[critical current density (mA·cm⁻ 2 [[ID=2>)]]> Comparative Example 1 <![CDATA[Pure PEO, no additives and no Li3PS4]]> 0.41 0.0008 0.01 Example 1 <![CDATA[Additive only, no Li3PS4]]> 0.64 0.0024 0.33 Example 2 <![CDATA[Additive + Moderate Li3PS4 Addition]]> 0.72 0.0045 0.54 Example 3 <![CDATA[Additive + Optimal Li3PS4 Addition]]> 0.92 0.0076 1.00
[0084] Experimental conclusions
[0085] 1. The pure PEO blank system (Comparative Example 1) has no modified components. It has the lowest lithium ion mobility, ionic conductivity, and dendrite resistance critical current density. It also has severe interfacial side reactions and cannot be adapted to lithium metal anodes.
[0086] 2. Adding only silicone organic conductive additives without introducing Li3PS4 sulfide (Example 1) only slightly improves the bulk ion conduction, but cannot form a stable SEI film on the lithium surface, and the critical current improvement is limited;
[0087] 3. Examples 2 and 3, which simultaneously combine silicone organic additives and Li3PS4 sulfidation additives, show a significant improvement in all three electrochemical indicators. With the optimization of Li3PS4 addition, additive dosage, and heat treatment process, the performance continues to improve. Example 3 represents the optimal process combination of this invention.
[0088] 4. Li3PS4 is the core component for in-situ construction of a stable SEI passivation layer, while the silicon organic additive is responsible for improving the lithium-ion conduction of the electrolyte. The two work together to solve the three major problems of poor ion conduction of PEO electrolyte, unstable lithium metal interface, and lithium dendrites. The anhydrous nitrogen preparation system avoids the hydrolysis and oxidation of sulfides, and the process is stable and suitable for large-scale thin film production.
[0089] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any technical solutions that involve simple adjustments, equivalent substitutions, or minor optimizations to parameters such as raw material ratios, drying temperatures, stirring times, additive amounts, and sulfide addition ratios within the core concept, synthesis, and interface modification principles of the present invention fall within the scope of protection defined by the claims of the present invention. Casting equipment, glove box specifications, electrochemical testing instruments, and pre-formation current parameters not detailed in this invention are all conventional and commonly used techniques in the field, and can be flexibly adjusted by those skilled in the art without creative effort. The Li3PS4 in-situ SEI composite polymer electrolyte prepared by this invention can be widely used in electrochemical devices such as lithium metal all-solid-state power batteries, solid-state energy storage batteries, and micro solid-state power supplies, possessing excellent electrochemical performance and industrial application value.
Claims
1. A method for preparing an in-situ generated SEI layer sulfide solid-state battery containing Li3PS4, characterized in that... Includes the following steps: A. In an anhydrous nitrogen-sealed reaction system, lithium sulfide (Li2S), elemental sulfur (S), and phosphorus pentasulfide (P2S5) were weighed according to their mass fractions, and ultra-dry acetonitrile solvent was added. The mixture was stirred at room temperature under a sealed environment to fully react and obtain a uniform yellow complex solution of Li3PS4. Water vapor and oxygen were isolated throughout the process. B. Preparation of composite polymer sulfurized electrolyte by casting: PEO and LiTFSI lithium salts are pre-dehydrated under vacuum; PEO and LiTFSI are dissolved in ultra-dry acetonitrile and stirred at a constant temperature to form a base solution; the above-mentioned Li3PS4 complex solution and silicon organic ionic conductivity additive are added to the base solution and stirred thoroughly at a constant temperature; the mixed solution is cast onto a PTFE substrate and dried in sections at room temperature and under vacuum under nitrogen protection to obtain a flexible composite solid electrolyte membrane; C. Battery assembly and in-situ SEI formation: Lithium / / - lithium symmetric batteries were assembled in an argon glove box with lithium metal as the negative electrode. Low-current pre-formation induced the in-situ formation of a stable SEI passivation layer containing Li3PS4 on the surface of the lithium metal. The lithium-ion mobility, room temperature ionic conductivity, and critical current density were tested using an electrochemical workstation.
2. The preparation method according to claim 1, characterized in that: Step A: The mass ratio of lithium sulfide, elemental sulfur, and phosphorus pentasulfide is 23~69:32~96:111~333.
3. The preparation method according to claim 1, characterized in that: Step A: Add 300-800 parts by weight of ultra-dry acetonitrile.
4. The preparation method according to claim 1, characterized in that: Step A: Stir in a sealed container at room temperature for 6-12 hours until the reaction is complete.
5. The preparation method according to claim 1, characterized in that: Step B: PEO drying conditions: 50~60℃, vacuum, 36~72h; LiTFSI drying: 100~120℃, vacuum, 36~72h.
6. The preparation method according to claim 1, characterized in that: Step B: PEO, LiTFSI, and ultra-dry acetonitrile mass fractions 60-80: 2.8-5.6: 150-250.
7. The preparation method according to claim 1, characterized in that: Step B: The base adhesive solution is stirred at a temperature of 50~60℃ for 6~18 hours.
8. The preparation method according to claim 1, characterized in that: Li3PS4 yellow solution, ionic conductivity additive, PEO base adhesive liquid mass parts 0~20: 0.1~0.2: 100~200; 0 parts correspond to a blank system without vulcanizing additives.
9. The preparation method according to claim 1, characterized in that... Step B: Preparation of ionic conductivity enhancer. Raw material mass parts: (4-vinylphenyl)dimethylsilane 16-32 parts, N-vinylcarbazole 19-20 parts, 1,1'-di(dimethylsilyl)ferrocene 0.3-1.5 parts, anhydrous THF 160-250 parts; Preparation process: T1 Catalyst activation: 0.1-0.3 parts of chloroplatinic acid H2PtCl6・6H2O, after vacuum dehydration, is mixed with 5-8 parts of anhydrous isopropanol and stirred at 40℃ for 30 min to obtain anhydrous platinum catalyst solution; T2 Hydrosilylation: Under nitrogen protection, organosilicon monomer, carbazole monomer, and ferrocene silane are added sequentially at a speed of 250-350 rpm; the temperature is increased to 50-60℃ at 3-5℃ / min and maintained for 2-4 h; T3 Purification and drying: THF and isopropanol are removed by vacuum distillation, and the mixture is washed with anhydrous ethanol for 3 hours. The silicon-organic conductive additive was obtained by vacuum drying at 60°C for 12 hours.
10. The preparation method according to claim 8, characterized in that: After mixing, stir the total adhesive solution at 50~60℃ for 6~18 hours.
11. The preparation method according to claim 1, characterized in that: After casting the adhesive solution, dry it at room temperature under nitrogen protection for 36-72 hours, and then dry it in a vacuum oven at 50-60°C for 36-72 hours to completely remove the acetonitrile solvent.